Problem-based learning, self- and peer assessment in higher education: towards advancing lifelong learning skills. Issue 3 (4th May 2022) - Alt, Dorit; Raichel, Nirit
ABSTRACT: This study sought to delineate the implementation of Problem-Based Learning (PBL) and peer- and self- assessment in a teacher training programme. This intervention was accompanied by measuring the participants' perceptions of the PBL environment and the assessment methods used compared with those of other courses they were previously enrolled in. Another aim was to reveal the most effective perceived PBL constructivist activities in enhancing the assessment methods. Data were gathered from 61 second-year students in a M.Ed. study track by the Constructivist Learning in Higher Education Settings Questionnaire (CLHES), the Peer- and Self- Assessment Questionnaire, and reflective journals. Quantitative results have shown that the PBL related activities were more pronounced in the designed intervention than in previous courses the students were enrolled in. Large effect size results were found for the perceptions of the peer- and self- assessment factors. Social interaction was found connected to the peer assessment variable; whereas Cooperative dialogue was related to the self-assessment construct. Analysis of the students' reflective journals revealed three key categories: 1. Knowledge and lifelong learning skills; 2. Social and cultural aspects of joint learning; 3. Perceptions of peer assessment, self-assessment and instructor's assessment. Implications, limitations, and suggestions for future studies are discussed.